Cabaran penyusuan dan penyelesaiannya - Jamani, Nurjasmine Aida (2016)
-Penyusuan susu ibu (PSI) amat disarankan seperti mana yang termaktub dalam Surah Al Baqarah Ayat 233 -Pertubuhan Kesihatan Sedunia juga menyarankan PSI -American Academy of Pediatric recommends exclusive breastfeeding for about 6 months, followed by continued breastfeeding as complementary foods are introduced, with the continuation of breastfeeding as complementary foods are introduced, with the continuation of breastfeeding for 1 year or longer as mutually desired by mother and instant.